Gastrointestinal Development and Microbiota Responses of Geese to Honeycomb Flavonoids Supplementation - He, Chenxin; Wu, Huadong; Lv, Yaning; You, Hongnan; Zha, Liqing; Li, Qin; Huang, Yani; Tian, Jinghong; Chen, Qiuchun; Shen, Yiwen; Xiong, Shiyuan; Xue, Fuguang (Frontiers in Veterinary Science, 2021)
Bacground: Geese are conventionally considered as herbivority which could also be raised with concentrate feeding diets without green grass because of the similar gastrointestinal tract with other poultry. However,the geese gut microbiota profiles and their interactions with epithelial cells are still of limited study. Flavonoids were well ducumented to shape gut microbiota and promote epithelial barriers functions individually or cooperatively with other metabolites. Therefore in the present study, honeycomb flavonoids(HF) was supplemented to investigate the effects on growth performances, intestinal development, and gut microbiome of geese. Material and Methods: Total of 400 one-day-old male lion-head geese with the similar birth weight (82.6g±1.4g) were randomly divided into 5 treatments: the control treatment (CON) and the HF supplementation treatments, HF was supplemented arithmetically increase from 0.25%-1%. Growth performance, carcass performances, and intestines’ development parameters were measured to determine the optimum supplement. Junction proteins including ZO-1 and ZO-2 and cecal microbiota were investigated to demonsrate the regulatory effects of HF on both microbiota and intestinal epithelium. Results: Results showed that 0.5% of HF supplement performed the superior Growth performance, carcass performances,and the total parameters of gastrointestinal development to other treatments. Further research showed that tight junction proteins including ZO-1 and ZO-2 significantly up-regulated, while Firmicutes, and some probiotics including Clostridiales, Streptococcus, Lachnoclostridium, and Bifidobacterium remarkably proliferated after HF supplement. In conclusion, HF supplement in concentrate-diet feeding geese effectively increased the growth performances by regulating the gut microbiota to increase the probiotic abundance to promote the nutrient degestibility, and fortifying the epithelial development and barrier functions to factilitate the nutrient absoption and ultilization.